(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2020)
Popular beliefs are an important subject that can be discontinued for its money from the impact in the social and psychological reality of the lives of individuals, each community, whatever the degree Its development or delay is a pattern of ideas and beliefs that its members believe in, which play a prominent role in the formation of the culture of that society, as well as reflect its members’ view of life. Beliefs that people believe vary and extend to various aspects of their psychosocial life, such as water-related beliefs, animal-related beliefs, beliefs associated with the supernatural or the supernatural world, beliefs related to optimism and pessimism, envy (eye injury), and beliefs related to the life cycle. Each of these beliefs plays a prominent role in human life and expresses the culture of its adherents. Beliefs related to optimism and pessimism, and their impact on human behavior if they often become the basic orientate of the behavior of some individuals regardless of their age and educational levels. The research relied on the descriptive and analytical approach by describing the beliefs of the members of the research community, and analyzing the functional role of beliefs related to optimism and pessimism in human life. تعد المعتقدات الشعبية من الموضوعات الهامة التي يمكن التوقف عندها لمالها من تأثير في الواقع الاجتماعي والنفسي لحياة الأفراد، فلكل مجتمع مهما بلغت درجة تطوره أو تأخره نسق من الأفكار والمعتقدات التي يؤمن بها أفراده، والتي تؤدي دوراً بارزاً في تكوين ثقافة ذلك المجتمع، كما تعكس نظرة أفراده للحياة. وتتنوع المعتقدات التي يؤمن بها الإنسان، وتمتد لتطال مختلف جوانب حياته النفسية والاجتماعية، كالمعتقدات المرتبطة بالماء، والمعتقدات المرتبطة بالحيوان، والمعتقدات المرتبطة بالجان أو العالم ما فوق الطبيعي، والمعتقدات المرتبطة بالتفاؤل والتشاؤم، والحسد (الإصابة بالعين)، والمعتقدات المرتبطة بدورة الحياة. وكل من هذه المعتقدات تؤدي دوراَ بارزاً في حياة الإنسان وتعبر عن ثقافة معتنقيها، ويعد كل من التفاؤل والتشاؤم عنصراً أساسيا من عناصر الحياة النفسية والاجتماعية بالنسبة لكل منا، ولا يمكن لحياة أي إنسان أن تخلو من أي من هذين العنصرين، وتأتي أهمية هذه الدراسة من أهمية المعتقدات المتعلقة بالتفاؤل والتشاؤم، وتأثيرها في سلوك الإنسان إذا تصبح في كثير من الأحيان الموجه الأساسي لسلوك بعض الأفراد بغض النظر عن أعمارهم ومستوياتهم التعليمية. اعتمد البحث على المنهج الوصفي التحليلي من خلال وصف للمعتقدات التي يؤمن بها أفراد مجتمع البحث، وتحليل الدور الوظيفي الذي تؤديه المعتقدات المتعلقة بالتفاؤل والتشاؤم في حياة الإنسان.